Setting New Delhi's Sail: A Realism Perspective of India's Pivot towards Israel - Gultom, Yosua Saut Marulitua; Manullang, Abel Josafat; Pradana, Muhammad Erza (Department of International Relations, Universitas Brawijaya, 2025)
Since its escalation on October 7th, 2023, the Israel-Palestine conflict has become a pivotal event, drawing global attention and complicating post-COVID international relations. India's historical stance of nonalignment, rooted in anti-colonialism and southern solidarity, has traditionally favored Palestinian independence. However, since the 1990s, India has gradually shifted its foreign policy, deepening ties with Israel amidst evolving geopolitical dynamics. This paper explores the factors driving India's shift towards stronger relations with Israel through a realist perspective. This paper employs the qualitative research methods with literature studies using primary and secondary data. The paper examines India's strategic adaptations in response to its rivalries with China and Pakistan. It finds that under BJP leadership, India's relationship with Israel has flourished, marked by extensive diplomatic exchanges and significant arms trade, making Israel a crucial ally in India's defense modernization. This partnership has provided India with critical military capabilities and technological advancements. The authors conclude that India's pursuit of strategic autonomy allows it to maintain agency and pursuit of national interests with little to none external restraints. This strategic autonomy approach underscores India's commitment to enhanced security and technological self-sufficiency amidst regional and global power shifts.